The Relationship Between Breast Anatomy Knowledge and Lactation Management Techniques on Breast Milk Production in Breastfeeding Mothers - Elvira Dwi Septia; Dessi Irmala Sari; Vivi Oktari (Indonesian Journal of Global Health Research, 2026)
The success of exclusive breastfeeding depends heavily on the mother’s understanding of breast anatomy and the application of proper lactation management techniques. This study aims to analyze the relationship between breast anatomy knowledge and lactation management techniques on breast milk production in breastfeeding mothers. The study used a quantitative cross-sectional design involving 65 breastfeeding mothers with infants aged 0–6 months. The sampling technique used was purposive sampling, in which participants were selected based on predetermined inclusion criteria relevant to the study objectives. Data collection was conducted using a structured and validated questionnaire covering knowledge of breast anatomy, lactation management techniques, and indicators of breast milk production. Data analysis was performed using the Spearman correlation test and multiple logistic regression. The results showed a significant relationship between breast anatomy knowledge and breast milk production, as well as a significant association between lactation management techniques and breast milk production. Simultaneous analysis indicated that both variables collectively contributed 62.8% to breast milk production, with lactation management techniques demonstrating the most dominant influence.